2020
DOI: 10.3390/pharmacy8040221
|View full text |Cite
|
Sign up to set email alerts
|

Can We Create a Circular Pharmaceutical Supply Chain (CPSC) to Reduce Medicines Waste?

Abstract: Background: The increase in pharmaceutical waste medicines is a global phenomenon and financial burden. The Circular Economy, as a philosophy within the pharmaceutical supply chain, aims to promote waste reduction, maximise medicines value, and enable sustainability within this supply chain (increasing circularity). Circularity strategies for pharmaceuticals are not currently implemented in many countries, due to quality and safety barriers. The aim of this study was to determine whether the application of cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…Proper medicine return refers to returning unused or expired medicines stored at home to regular places, such as pharmacies, hospitals, etc., which residents rarely do at present [ 4 ]. Improper medicine return refers to directly discarding medicines, such as flushing medicines down the sink or toilet, throwing them in the kitchen bin, selling them, etc., which is the most common medicine return behavior of residents [ 3 , 4 , 5 ]. Proper medicine return and reuse can minimize hazards to the environment and reduce the overall cost of medicines to our society [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper medicine return refers to returning unused or expired medicines stored at home to regular places, such as pharmacies, hospitals, etc., which residents rarely do at present [ 4 ]. Improper medicine return refers to directly discarding medicines, such as flushing medicines down the sink or toilet, throwing them in the kitchen bin, selling them, etc., which is the most common medicine return behavior of residents [ 3 , 4 , 5 ]. Proper medicine return and reuse can minimize hazards to the environment and reduce the overall cost of medicines to our society [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alshemari found that only when every stakeholder in the medicine return system collaborates effectively can the whole system operate sufficiently. That includes pharmaceutical companies, distributors, retailers, pharmacies, logistics carriers, residents, and government departments [ 5 ]. According to the study of Bravo, pharmaceutical enterprises can cooperate with distributors and retailers to recover medicines at regular replenishment so as to reduce the round-trip transportation cost of medicines and optimize the medicine return system [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of production and inventory planning (Uthayakumar & Priyan, 2013 ) Lack of demand forecasting disturbs the demand and supply gap, resulting in overproduction and expired medications B8. The low shelf life of medicines (Alshemari et al, 2020 ) Low quality and quick expiry of the medicines B9. Difficulty in the visibility of the supply chain (Sara et al, 2018 ) The complexity of the pharmaceutical supply chain makes it difficult to monitor the entire supply chain B10.…”
Section: Data Collection and Methodologymentioning
confidence: 99%
“…Effective segregation of medical waste on the consumer level would further ensure sustainable waste management practices such as recycling and reusing products. A good example of this can be the reusing and recycling of the outer packaging or cartage of inhalers (Alshemari et al, 2020 ). Supporting legislation from the government bodies can be beneficial in improving the overall RL infrastructure, a good example of which can be the supporting laws in Portugal (Niza et al, 2014 ).…”
Section: Data Collection and Methodologymentioning
confidence: 99%
“…Redistributing unused medications can reduce healthcare waste and costs, and enhance access to care [15][16][17][18][19][20][21][22]. Patients are recognized as the primary consumers of reused medications and as one of the potential primary sources of medications to be reused [23][24][25][26][27]. Therefore, understanding the interplay between patients and their medications will clarify the types of risk that medication reuse can minimize, guide its efficient implementation, and illuminate its benefit.…”
Section: Introductionmentioning
confidence: 99%